The SVR (Self-Video Recording) Technique to Enhance Self-Confidence in English Speaking Proficiency - Noor Sahid Kusuma Hadi Manggolo; Dwitiya Ari Nugrahaeni; Afi Normawati; Nurul Ngaini Khusniyati (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
This explanatory sequential mixed-method study tackles the English language proficiency challenge faced by non-English major students, emphasizing the critical role of the college phase in shaping the pre-professional skills of Indonesian youth. It aims to assess whether the Self-Video Recording (SVR) technique can boost the self-confidence of them when speaking English. The research directly assesses first-year students at Universitas Tidar. The primary focus is on evaluating SVR's positive impact on self-assurance in English communication. Based on the data compiled, there is a consistent trend in the responses from students who participated in both the questionnaire and the interview. Out of the 65 students, it was reported that their confidence levels increased after undergoing the interventions carried out by the research team. This indicates that the majority of students who reacted positively to the role-play exercises and the implementation of the SVR technique to enhance their confidence in speaking English are likely the same group of students. Hence, it is plausible to consider that the research participants who observed only a slight improvement cannot be solely attributed to external factors but may also be influenced by internal factors, such as a lack of interest in speaking English and other related considerations.